Genome-wide identification and expression analysis of GDP-D-mannose pyrophosphorylase and KATANIN in Corymbia citriodora - Wang, Chubiao; Luo, Jianzhong; He, Wenliang; Huang, Anying; Lu, Wanhong; Lin, Yan; Ou, Yuduan (Frontiers in Plant Science, 2023)
The GDP-D-mannose pyrophosphorylase (GMP) and microtubule severing enzyme KATANIN (KTN) are crucial for wood formation. Although functional identification has been performed in Arabidopsis, few comprehensive studies have been conducted in forest trees. In this study, we discovered 8 CcGMP and 4 CcKTN genes by analyzing the whole genome sequence of Corymbia citriodora. The chromosomal location, genome synteny, phylogenetic relationship, protein domain, motif identification, gene structure, cis-acting regulatory elements, and protein-interaction of CcGMP and CcKTN were all investigated. KTN has just one pair of segmentally duplicated genes, while GMP has no duplication events. According to gene structure, two 5' UTRs were identified in CcGMP4. Furthermore, there is no protein-interaction between KTN and GMP. Based on real-time PCR, the expression of most genes showed a positive connection with DBH diameters. In addition, the expression of CcGMP4 and CcKTN4 genes were greater in different size tree, indicating that these genes are important in secondary xylem production. Overall, this findings will enhance our comprehension of the intricacy of CcGMP&CcKTN across diverse DBHs and furnish valuable insights for future functional characterization of specific genes in C. citriodora.